Lady Friday [compact disc, unabridged] - Nix, Garth (Nix, Garth. Keys to the kingdom (Listening Library), 2007)
Young Arthur Penhaligon must weigh an offer from Lady Friday that is either a cunning trap for the Rightful Heir or a golden opportunity that he must seize.